2010
DOI: 10.1002/fuce.201000107
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electrical Conductivity of Trivalent Rare‐earth Cation‐doped Neodymium Zirconate by Co‐doping Gadolinium and Ytterbium

Abstract: Pyrochlore oxides of A2Zr2O7, where A represents trivalent rare‐earth elements, have a high electrical conductivity, which makes them suitable for applications as high‐temperature solid electrolytes. The influence of Gd and Yb cations co‐doping at the Nd site on structure and electrical conductivity of a pyrochlore oxide Nd2Zr2O7 is investigated using X‐ray diffraction and impedance spectra measurements. Different zirconate ceramics of Nd2Zr2O7, Nd1.8Gd0.2Zr2O7, Nd1.8Gd0.1Yb0.1Zr2O7, Nd1.4Gd0.6Zr2O7 and Nd1.4G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…3 The intercepts of the arcs with the real axis would yield the value of resistance, R, from which the conductivity of the materials can be calculated using the relation,…”
Section: View Article Onlinementioning
confidence: 99%
“…3 The intercepts of the arcs with the real axis would yield the value of resistance, R, from which the conductivity of the materials can be calculated using the relation,…”
Section: View Article Onlinementioning
confidence: 99%
“…6)11),13), 14) Yamamura et al 6) have reported the oxide-ion conductivity of the fluorite or pyrochlore phases in the Ln 2 Zr 2 O 7 and (Ln 1¹x LnB x ) 2 -Zr 2 O 7 (Ln, LnB = La, Nd, Gd, Eu, Sm, Y and Yb) systems. They concluded that the oxide-ion conductivity increased with increasing ionic radius ratio in the fluorite phase range, showed the sharp maximum (Eu 2 Zr 2 O 7 showed the highest conductivity of 8.3 © 10 ¹3 S/cm at 1073 K) in the vicinity of the phase boundary in the pyrochlore phase range, and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In the ideal case, the frequency dependent complex admittance of polycrystalline electrolytes can be modelled by a resistor-capacitor (RC) pair in parallel. However, in the present case, in place of capacitor a constant phase element (CPE) is required to model the experimental data [20], as shown in Figure 2( 7 , respectively, which correspond to the grain contributions. The impedance spectra of (Nd 1-x Gd x ) 2 (Ce 1-x Zr x ) 2 O 7 ceramics show only a single semicircle, suggesting that the contribution from the resistance of grain boundary was negligibly small.…”
Section: Resultsmentioning
confidence: 99%
“…These properties make A 2 B 2 O 7 -type oxides suitable for extensive applications such as hightemperature thermal barrier coating materials, catalysts and solid electrolytes, etc. [2][3][4][5][6][7]. The intrinsic anion vacancy enables A 2 B 2 O 7 -type oxides possess high electrical conductivity, and can be considered as a potential candidate for solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%